P01.121 Optune treatment does not affect quality of life in treatment of high grade glioma compared to chemo-radiotherapy alone. (19th September 2018) - Onken, J; Goerling, U; Heinrich, M; Guenes, S; Krex, D; Vajkoczy, P; Misch, M
Abstract: Background: Tumor treating fields (optune) significantly prolong progression-free and overall survival in patients with newly diagnosed glioblastoma (GBM). Critics claim optune significantly lowers patients' quality of life (QOL) due to side effects and average daily time on therapy. However, very limited data exist on how QOL is rated by patients under optune treatment in GBM therapy. Material and Methods: 27 patients with primary GBM (n=13) or recurrent high grade glioma (rHGG, n=14) have been treated with optune. QOL was assessed using EORTC questionnaires QLQ-C30, BN20, FA13 (fatigue), and SSUK-8 (social support) plus a device-specific questionnaire. Results were compared to 27 patients under primary GBM therapy without optune. Analysis was carried out accordding to the EORTC manual. Results: Optune treated patients did not rate their QOL worse than control. Emotional functioning was clinically relevant better in the optune group. In symptom scales optune patients did not fare worse than control but experienced significantly less fatigue and received more positive social support. Device alarms occured 3.56 times per 24h, 2.29 during night. Alarms were rare (2–3 per week) in 29.6% and often (more than 3x week) in 37% of patients. Moderate or no alarm discomfort numbered 62.9% and severe in 29.6%. Weight (44.4%) and size (33.3%) of the device were seen as compliance barriers a few times per week or more often. 55.5% were annoyed by array change rate. Average time for array changes was 49.92 minutes (n = 25; median 30 minutes) and caused severe discomfort in 25.9%. Therapy was willingly paused during daytime in 66.7% and in 11.1% at night. Daily time on therapy restricted daily routine life moderately in 48.1% and severely in 25.9% of patients. Hair shaving was no issue in >85%. A total of 74% felt moderate or no discomfort by therapy side effects. Working life, hobbys, mobility were affected moderately (<25% of users), sexual life was significantly affected in nearly half of the patients (48.1%). However, therapy motivation was high and social life was stable (, , no" or, , minor" obstacles in 66.6%). QOL generally dropped in the 1st month under therapy and then recovered after an, , adjusting phase". 74.1 % of patients would recommend optune therapy to others, 18 without restrictions. 66.7% would do optune therapy again, 4 patients would not repeat treatment. Conclusion: In general, the addition of optune treatment did not worsen quality of life in comparison to other patients under first line glioblastoma therapy. Although optune treatment frequently affects daily life in all aspects, most patients did not rate these events as severely discomforting. This may be explained by a repeated and honest consultation strategy before treatment start. Improval of some aspects of therapy (carrying the device, battery life, temperature alarms) may further increase acceptance, compliance and patient satisfaction.